The Effects of Partial Hip Replacement Surgery After Hip Fractures on Complete Blood Count Parameters in Elderly - Sayit, E.; Terzi, Y. (E-Century Publishing Corporation 40 White Oaks Lane Madison WI 53711, 2017)
The aim of this study is to assess the complete blood cell parameters of patients undergoing partial hip replacement surgery due to hip fractures and to analyze and compare the changes in these parameters upon admission to the hospital, after surgery, and before discharge. Twenty-two complete blood count parameters of the 40 patients who underwent partial hip replacement surgery due to hip fracture upon admission to the hospital, 12 hours after surgery, and prior to discharge from the hospital were analyzed and compared. When we compared the hemoglobin, hematocrit, red blood cell (RBC) counts, and the red blood cell distribution width (RDW) between the groups, we found significant differences (P < 0.05). Of the parameters relating to the white blood cell (WBC) counts and percentages, most parameters had significant differences (P < 0.05). There was a significant difference in only the results of the platelet counts after surgery, and prior to discharge (P < 0.05). Analyzing the complete blood count parameters during partial hip replacement surgery due to fractures may help in understanding the physiological effects of the fracture and the procedure. While fractures and hip replacement surgery each cause some changes, hip replacement surgery after fractures does not cause any secondary changes in most blood cells. © 2017, E-Century Publishing Corporation. All rights reserved.
Keywords: Complete Blood Count; Hip; Hip Fracture; Hip Replacement